2016
DOI: 10.1016/j.spa.2016.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The gap between Gromov-vague and Gromov–Hausdorff-vague topology

Abstract: Abstract. In [ALW15] an invariance principle is stated for a class of strong Markov processes on tree-like metric measure spaces. It is shown that if the underlying spaces converge Gromov vaguely, then the processes converge in the sense of finite dimensional distributions. Further, if the underlying spaces converge Gromov-Hausdorff vaguely, then the processes converge weakly in path space. In this paper we systematically introduce and study the Gromov-vague and the Gromov-Hausdorff-vague topology on the space… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 30 publications
(34 reference statements)
0
73
0
Order By: Relevance
“…As mentioned in Remark 3.20, this method gives more quantitative bounds in the arguments. Despite some similarities in the arguments (which are also similar to those of [1] and other literature that use the localization method to generalize the Gromov-Hausdorff metric), the results of [5] do not give a metrization of the Gromov-Hausdorff-Prokhorov topology on M * and do not imply its Polishness. Also, the Strassen-type theorems (Theorems 2.1 and 3.6) and the results based on them are new in the present paper.…”
Section: The Gromov-hausdorff-vague Topologymentioning
confidence: 57%
See 1 more Smart Citation
“…As mentioned in Remark 3.20, this method gives more quantitative bounds in the arguments. Despite some similarities in the arguments (which are also similar to those of [1] and other literature that use the localization method to generalize the Gromov-Hausdorff metric), the results of [5] do not give a metrization of the Gromov-Hausdorff-Prokhorov topology on M * and do not imply its Polishness. Also, the Strassen-type theorems (Theorems 2.1 and 3.6) and the results based on them are new in the present paper.…”
Section: The Gromov-hausdorff-vague Topologymentioning
confidence: 57%
“…A second proof for Polishness of M ′ * can be given by Alexandrov's theorem by using Polishness of M * and by showing that M ′ * corresponds to a G δ subspace of M * (given n > 0, it can be shown that the set of (X, o, µ) ∈ M * such that ∀x ∈ X : µ(B 1/n (x)) > 0 is open). The method of [5] is different from the present paper. It defines the metric on M ′ * by modifying (3.13) (since (3.13) does not make M ′ * complete), but the definition in the present paper is based on the notion of PMM-subspaces, Lemma 3.12 and (3.11).…”
Section: The Gromov-hausdorff-vague Topologymentioning
confidence: 65%
“…We first prove convergence of the object of interest in the Gromov‐weak topology, essentially showing that for each fixed k ≥ 2, the distance matrix constructed from k randomly sampled vertices converges in distribution to the distance matrix constructed from k points appropriately sampled from the limiting structure. This result, coupled with a global lower mass bound implies via general theory that convergence occurs in the stronger Gromov‐Hausdorff‐Prokhorov sense. In the context of critical random graphs, this technique was first used in to analyze the so‐called rank‐one critical inhomogeneous random graph.…”
Section: Discussionmentioning
confidence: 99%
“…The notion for convergence is the one given by the spatial Gromov-Hausdorff-vague metric. For details, see [7,27].…”
Section: Resistance Network and Convergence Of Processesmentioning
confidence: 99%